Are supply chain vulnerabilities increasing in the era of geoeconomic fragmentation? - Tuuli McCully; Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We examine changes in the manufacturing sector value chains of the EU, US, China, and India between 2018 and 2023 by introducing three metrics for supply-chain vulnerability. For our first metric, the physical length of a supply chain based on the distance between the producer of the final product and input source country, we find modest evidence of near-shoring for the US, EU, and India. Second, utilizing political distances between the supply chain participants, our assessment of the geopolitical risks of supply chains reveals slight friend-shoring by the US and EU, mainly a result of Russia's reduced participation in their supply chains. Third, looking at the already extensive supply chain diversification of the studied countries, we find diversification has increased modestly since 2018.
urn:nbn:fi-fe2024112797201
Keywords: 330; global value chains; supply chains; fragmentation; value-added trade; input-output